2020
DOI: 10.1002/pi.6139
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)/graphene oxide nanocomposite hydrogel with catalytic activity: the removal behavior and dual adsorption/catalytic degradation mechanism for dye wastewater

Abstract: The treatment of dye wastewater with traditional adsorption materials usually proceeds slowly with low removal efficiency and without completely eliminating dye molecules, leading to secondary pollution. In this work, poly(vinyl alcohol)/graphene oxide@tetraamino iron phthalocyanine (PVA/GO@TAFePc) nanocomposite hydrogels with catalytic activity were prepared via an in situ crosslinking method. Through interfacial covalent and π–π interactions, TAFePc was loaded onto GO layers with a high loading ratio, and GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…In addition, the surface area of PVA/GO hydrogel was 31.616 m 2 g −1 , which was higher than 8.163 m 2 g −1 reported by Yu et al. [48] . The surface area of PVA/GO/aloe vera hydrogel was meaningfully lower than the PVA/GO hydrogel, about 10 % of the parental composite, with lower pore volume.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, the surface area of PVA/GO hydrogel was 31.616 m 2 g −1 , which was higher than 8.163 m 2 g −1 reported by Yu et al. [48] . The surface area of PVA/GO/aloe vera hydrogel was meaningfully lower than the PVA/GO hydrogel, about 10 % of the parental composite, with lower pore volume.…”
Section: Resultscontrasting
confidence: 52%
“…[47] In addition, the surface area of PVA/GO hydrogel was 31.616 m 2 g À 1 , which was higher than 8.163 m 2 g À 1 reported by Yu et al. [48] The surface area of PVA/GO/aloe vera hydrogel was meaningfully lower than the PVA/GO hydrogel, about 10 % of the parental composite, with lower pore volume. However, according to the UV/Vis adsorption analysis, the acceleration of MB adsorption was higher in PVA/GO/aloe vera hydrogel, indicating the more effective role of functional groups compared to the surface area of the hydrogel containing aloe vera.…”
Section: Chemistryselectmentioning
confidence: 87%
“…Yu et al regulated the content of GO@TAFePc in PVA/GO@TAFePc hydrogels and obtained gel structures with different pore sizes and porosity. The removal rate of methylene blue was up to 98% [ 87 ]. Several studies have shown that adding metal oxides can effectively improve the dye removal rate.…”
Section: Applicationsmentioning
confidence: 99%
“…Nanocomposite hydrogel (NC hydrogel), nanomaterials are incorporated in the cross‐linked polymeric chains, is one type of emerging hydrogels to present unique properties compared to traditional polymeric hydrogel. [ 1–4 ] NC hydrogels with different nanomaterials (e.g., carbon‐based nanomaterials, [ 5–8 ] polymer nanoparticles, [ 9 ] inorganic/ceramic nanoparticles, [ 10–12 ] or metal/metal oxide nanoparticles [ 13–15 ] ) present improved mechanical toughness [ 16,17 ] as well as novel performances (e.g., magnetic responsiveness, [ 13,18 ] near‐infrared responsiveness, [ 19–22 ] antimicrobial properties, [ 23,24 ] electricity, [ 25 ] thermal conductivity, [ 26 ] and fluorescence [ 27,28 ] ) for specific applications. Those “smart hydrogels” that respond to internal and external stimuli (e.g., light, [ 29,30 ] pH, [ 31–33 ] temperature, [ 34,35 ] or magnetic field [ 36,37 ] ) have been widely used in tissue engineering, [ 38,39 ] biosensors, [ 40,41 ] and drug delivery.…”
Section: Introductionmentioning
confidence: 99%